2021
DOI: 10.1371/journal.pone.0261744
|View full text |Cite
|
Sign up to set email alerts
|

Baseline knowledge and attitudes on COVID-19 among hotels’ staff: A cross-sectional study in Kigali, Rwanda

Abstract: Background The World Health Organization declared coronavirus disease 2019 (COVID-19) as a global pandemic on the 11th of March, 2020. Hotels and other public establishments have been associated with higher transmission rates. Sensitisation of staff and strengthening of Infection Prevention and Control (IPC) practices in such settings are important interventions. This study assessed the baseline knowledge and attitudes on COVID-19 among hotels’ representatives in Kigali, Rwanda. Methods A cross-sectional stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In other studies, the educational level was reported to be associated with the COVID-19 knowledge among sub-Sahara African populations, 9,35 including urban Rwanda. 23 We also observed low access to adequate handwashing (35.6%), defined as living in a household with a handwashing station with regular access to water and soap. This finding is consistent with previous reports on disproportionate low proportions of households with access to water, soap and sanitation facilities in rural Rwanda.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In other studies, the educational level was reported to be associated with the COVID-19 knowledge among sub-Sahara African populations, 9,35 including urban Rwanda. 23 We also observed low access to adequate handwashing (35.6%), defined as living in a household with a handwashing station with regular access to water and soap. This finding is consistent with previous reports on disproportionate low proportions of households with access to water, soap and sanitation facilities in rural Rwanda.…”
Section: Discussionmentioning
confidence: 79%
“…Our findings suggest much poorer knowledge about COVID-19 among rural patients with chronic diseases compared to the findings from two studies on COVID-19-related knowledge, attitudes and practices (KAP) among hotels' staff and HIV patients receiving clinical follow-up at a hospital in Kigali City. 22,23 There are several reasons for this discrepancy. First, the KAP studies for hotels' staff and HIV patients were conducted three and four months after our study was completed, respectively, and proper knowledge about COVID-19 could have grown over this time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation